A study on Ecotect application of local climate at a residential area in Chuncheon, Korea - Wu, Qian; Jo, Hyun-Kil (Journal of Environmental Engineering and Landscape Management, 2015)
The local climate data were investigated at a residential area in Chuncheon from May to October in 2013.In addition, the simulations were carried out by the Autodesk Ecotect Analysis tool. Site A had the lowest temperature in summer. The best building orientation was south by east 157.5°. Based on the photosynthetically active radiation(PAR) values day-neutral species should be planted around sites C and E, shade-tolerant species around site D and helioplous species around sites A and B. In addition, site A is the most comfortable place in the residential area with a predicted mean vote (PMV) value around 0. It was found that there were four main aspects to be considered for the residential designs which were building height, land cover, planting design and building orientation. Moreover, the results showed that local climate and shading conditions should be of great concern in design or improvement of residential areas. First published online: 17 Apr 2015